Open innovation in developing an early standardization of battery swapping according to the Indonesian national standard for electric motorcycle applications - Wahyudi Sutopo; Dana Prianjani; Fakhrina Fahma; Eko Pujiyanto; Amran Rasli; Tan Owee Kowang (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This research aims to achieve early standardization for battery swapping in line with domestic capabilities and global standards, and to protect Indonesian battery swap stakeholders. By distributing questionnaires to 190 respondents, the Framework for Analysis, Comparison, and Testing of Standards (FACTS) approach was used to analyze stakeholder needs, compare global standards regarding battery swaps, and validate the Indonesian National Standard (SNI) framework. An open innovation approach was considered to integrate a FACTS approach with open participation, mutual understanding, and consensus to generate parameters. Therefore, characteristics of open participation, mutual understanding, and consensus were identified using FACTS to catalyze market needs as well as stakeholder needs. The relationship between SNI implementation variables, national uniqueness, and stakeholder needs was predicted using structural equation modeling (SEM). We found that the proposed constructs-i.e., electromagnetic compatibility, equipment construction requirements, marking and instruction, and protection against electric shock-positively affect SNI implementation. Meanwhile, the SNI implementation, national uniqueness, and stakeholder protection positively affect SNI acceptance. Therefore, SNI acceptance can be obtained by considering SNI implementation, national uniqueness, and stakeholder protection. The findings of this study can be used to develop an SNI battery swap test that is globally competitive, has national characteristics, and considers domestic capabilities when developing the SNI documentation.
Keywords: 650; battery swap; early standardization; FACTS; global competitiveness; open innovation; SEM